SLAM/SAP Decreased Follicular Regulatory T Cells in Patients with Graves' Disease. (20th April 2021) - Geng, Lina; Yang, Jun; Tang, Xinyi; Peng, Huiyong; Tian, Jie; Hu, Zhigang; Liu, Yingzhao; Xu, Huaxi; Wang, Shengjun
Abstract : Signaling lymphocytic activation molecule (SLAM) and SLAM-associated protein (SAP) play important role in inflammatory and autoimmune diseases. Our study is aimed at detecting the expression of SLAM and SAP in patients with Graves' disease (GD) and analyzing the effect of SLAM/SAP on circulating blood CD4 + CXCR5 + Foxp3 + follicular regulatory T (Tfr) cells. The level of SAP in CD4 + CXCR5 + T cells and the level of SLAM on CD19 + B cells were significantly increased in the patients with GD, but no significant difference in the level of SLAM on CD4 + CXCR5 + T cells was observed between the patients with GD and the healthy controls. A decrease in the percentage of Foxp3 + cells in CD4 + CXCR5 + T cells was observed following anti-SLAM treatment, but the percentages of IFN- γ + cells, IL-4 + cells, and IL-17 + cells showed no obvious differences. The proportion of circulating Tfr cells was decreased in the patients with GD, and the proportion of circulating Tfr cells had a negative correlation with the level of SAP in CD4 + CXCR5 + T cells and the levels of autoantibodies in the serum of the patients with GD. Our results suggested that the SLAM/SAP signaling pathway is involved in the decrease of circulating Tfr cells in Graves' disease.